Intrinsic Self‐Trapped Emission in 0D Lead‐Free (C4H14N2)2In2Br10 Single Crystal - Zhou, Lei; Liao, Jin‐Feng; Huang, Zeng‐Guang; Wei, Jun‐Hua; Wang, Xu‐Dong; Chen, Hong‐Yan; Kuang, Dai‐Bin (Angewandte Chemie International Edition, 2019)
Low‐dimensional lead halide perovskite materials recently have drawn much attention owing to the intriguing broadband emissions; however, the toxicity of lead will hinder their future development. Now, a lead‐free (C4H14N2)2In2Br10 single crystal with a unique zero‐dimensional (0D) structure constituted by [InBr6]3− octahedral and [InBr4]− tetrahedral units is described. The single crystal exhibits broadband photoluminescence (PL) that spans almost the whole visible spectrum with a lifetime of 3.2 μs. Computational and experimental studies unveil that an excited‐state structural distortion in [InBr6]3− octahedral units enables the formation of intrinsic self‐trapped excitons (STEs) and thus contributing the broad emission. Furthermore, femtosecond transient absorption (fs‐TA) measurement reveals that the ultrafast STEs formation together with an efficient intersystem crossing has made a significant contribution to the long‐lived and broad STE‐based emission behavior. A lead‐free indium‐based (C4H14N2)2In2Br10 single crystal was synthesized and characterized; it has a unique 0D crystal structure. An intrinsic self‐trapped exciton‐based ultra‐broad photoluminescence has been observed as a result of an excited‐state structural distortion in [InBr6]3− octahedrons.